ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU MORAL KEAGAMAAN MAHASISWA - Magdalena, Magdalena (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractThis study aimed to determine influenced factors of the students? gender, organization participant, and education background, and to Islamic moral action. Based the data analysis, there are many findings. There was a correlation between students? gender, organization participant, and education background simultanly to Islamic moral action. Then, there was a different Islamic moral action based on the gender, organization participant, and education background.Kata Kunci: Perilaku moral keagamaan, jenis kelamin, status organisasi, latar belakang pendidikan.